Cardiac devices in patients with transthyretin amyloidosis: Impact on functional class, left ventricular function, mitral regurgitation, and mortality. (25th September 2019) - Donnellan, Eoin; Wazni, Oussama M.; Saliba, Walid I.; Baranowski, Bryan; Hanna, Mazen; Martyn, Michael; Patel, Divyang; Trulock, Kevin; Menon, Venu; Hussein, Ayman; Aagaard, Philip; Jaber, Wael; et al.
Abstract: Background: The aim of our study was to investigate outcomes of patients with ATTR (amyloidosis and transthyretin) CA (cardiac amyloidosis) and implantable devices with respect to left ventricular ejection fraction (LVEF), mitral regurgitation (MR), New York Heart Association (NYHA) functional class, and mortality. Methods: This was a retrospective observational cohort study of 78 patients with ATTR CA and implantable devices. During a mean follow‐up of 42 months we investigated the impact of right ventricular (RV) pacing burden and biventricular (BiV) pacing on LVEF, MR severity, NYHA functional class, and mortality. Results: Worsening MR occurred in 11% of patients with a RV pacing % <40% compared to 62% of those with a RV pacing burden >40% ( P  = .002). Similarly, worsening LVEF occurred in 26% of patients who were RV paced <40% and 89% of those who were RV paced >40% of the time ( P  < .0001) and worsening in NYHA functional class occurred in 22% and 89%, respectively ( P  < .0001). Improvement in LVEF, NYHA functional class, and MR severity occurred in 78%, 67%, and 67%, respectively, in those with BiV devices. Death occurred in 67% of patients in the cardiac resynchronization therapy group compared to 68% of those with a RV pacing burden <40% and 92% of those with a RV pacing burden >40%. Conclusion: A higher RV pacing burden is associated with deleterious remodeling and congestive heart failure in patients with ATTR CA, whereas BiV pacing is associated with improvements in LVEF, NYHA class, and degree of MR. BiV pacing should be considered in patients with ATTR CA and an indication for pacing. However, further larger prospective studies will need to be performed.